PARADIPLOMASI KOTA BANDUNG DALAM PERJANJIAN MILAN URBAN FOOD POLICY PACT (MUFPP) UNTUK PENGEMBANGAN SISTEM PANGAN BERKELANJUTAN - Dede Rohman; Kardina; Sulastri (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
This research aims to explain the implementation of policy and framework of the Milan Urban Food Policy Pact (MUFPP) with the Bandung City Government in the sustainable food system program. This research uses the concept of paradiplomacy and International Regime theory. The results of the research explain that the implementation of the MUFPP policy and framework is proceeding in accordance with the initial objectives of the City of Bandung for joining, namely the development of a sustainable food system program in three (3) policy categories and a 12-point framework or action recommendations that have been implemented by the City of Bandung. This global paradiplomacy has provided effective results by fulfilling the goal of a sustainable food system from the independence of the city of Bandung to reducing its food dependence.